Management of synchronous adenocarcinoma of the esophago-gastric junction and ampulla of Vater: case report of a surgically challenging condition - REYNOLDS, JOHN (BioMed Central, 2009)
We report herein a case of a synchronous presentation of an adenocarcinoma of esophagago-gastric junction type II and an ampullary tumor that was treated by combined Whipple's pancreaticoduodenectomy, total gastrectomy and esophagectomy. The magnitude of this operation was safely achieved with meticulous surgical techniques and perioperative care without any major short or long term complications. Patient returned to a good quality of life at six-month follow up with no further gastrointestinal symptoms or evidence of disease recurrence.
PUBLISHED
Keywords: Surgery